Influence of time factor and albuminuria on characteristics of patients with type 2 diabetes Mellitus before, during and 1 year after COVID-19 recovery - Mohammed Ali Gameil; Rehab Elsayed Marzouk; Ahmed Hassan El-Sebaie; Ahmed Ahmed Ahmed Eldeeb (Diabetology & Metabolic Syndrome, 2023)
Abstract Background The potential effects of time factor and albuminuria on the morbid alterations in patients with type 2 diabetes (T2D) and COVID-19 are still unclear. We aimed to address the morbid alterations and the potential effects of time factor and albuminuria on the patients’ characteristics before, during, and 1 year after COVID-19 recovery. Methods 83 patients with T2D were included, at Mansoura University Hospital, Egypt (July 2021-December 2021). Data of detailed history, physical examination, laboratory tests were recruited from files of the patients. Diagnosis and resolution of COVID-19 were established by Real time polymerase chain reaction (RT-PCR) test of SARS-CoV2. Complete blood count (CBC), renal and hepatic function tests, multiple measures of morning spot urine albumin to creatinine ratio (urine ACR), glycosylated hemoglobin (HBA1c), lipid profile, erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), Ferritin, neutrophil to lymphocyte ratio (NLR), vitamin D3, intact parathyroid hormone (intact PTH), serum calcium were applied to all participants. Results Our participants had a mean age of 45 years, 60.2% male, 56.6% were hospitalized, and 25.3% were admitted to ICU for severe COVID-19. Albuminuria was prevalent in 71.1% before, 98.8% during, and 92.8% after COVID-19 recovery. Patients with albuminuria showed older age, longer duration of T2D, more frequent severe COVID-19 and hospitalization (p = 0.03, p < 0.001, p = 0.023& p = 0.025) respectively. Body mass index (BMI), mean arterial blood pressure, ESR, CRP, ferritin, NLR, HBA1c, triglycerides to high-density lipoprotein cholesterol (TG/HDL-C) ratio, vitamin D3, serum calcium, alkaline phosphatase (ALP), hepatic aminotransferases, and urine ACR showed significant alterations throughout the study (p < 0.001 for all). Although the interaction between time and albuminuria showed non-significant effect on all studied parameters, we noticed relevant main effects of time factor on Body mass index (BMI), HBA1c, glomerular filtration rate (eGFR), TG/HDL ratio, NLR, vitamin D3, (p < 0.001 for all). Moreover, albuminuria showed main effects on BMI, serum creatinine, and intact PTH (p = 0.019, 0.005 & <0.001), respectively. Conclusion The characteristics of patients with T2D significantly altered throughout the study. Time factor and albuminuria exerted relevant main effects on the patients’ characteristics without significant effect of their interaction.